2022
DOI: 10.13057/biodiv/d230261
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of an agroforestry system with 2-year-old sengon (Paraserianthes falcataria) and shade-tolerant upland rice

Abstract: Abstract. Tsaniya SH, Wijayanto N, Wirnas D. 2022. An evaluation of an agroforestry system with 2-year-old sengon (Paraserianthes falcataria) and shade-tolerant upland rice. Biodiversitas 23: 1159-1166. Sengon is tree species that is often cultivated with upland rice in agroforestry systems. The main obstacle of rice development in agroforestry systems are competition between plants for sunlight and nutrients. 2-year-old sengon has a wider canopy and longer roots, increasing competition between sengon and rice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Soybean plants are plants that require full sun to grow normally, but can still grow at a certain level of shade. The development of soybean plants as intercropping crops or intercrops is an alternative to increase soybean production [14]. Observations of soybean plants were carried out on the ability of viable soybean seeds to germinate.…”
Section: Resultsmentioning
confidence: 99%
“…Soybean plants are plants that require full sun to grow normally, but can still grow at a certain level of shade. The development of soybean plants as intercropping crops or intercrops is an alternative to increase soybean production [14]. Observations of soybean plants were carried out on the ability of viable soybean seeds to germinate.…”
Section: Resultsmentioning
confidence: 99%
“…Sengon seedlings aged seven months with a plant height of ±50 cm resulted in reduced light penetration to rice plants under sengon. In the agroforestry pattern of sengon and upland rice, there is competition for sunlight, nutrients, and water (Dewi et al 2017;Tsaniya et al 2022). In their research findings of Tsaniya et al (2022), it was observed that the height of upland rice plants was lower in agroforestry compared to monoculture rice.…”
Section: Growth Of Sengon and Upland Ricementioning
confidence: 99%
“…In the agroforestry pattern of sengon and upland rice, there is competition for sunlight, nutrients, and water (Dewi et al 2017;Tsaniya et al 2022). In their research findings of Tsaniya et al (2022), it was observed that the height of upland rice plants was lower in agroforestry compared to monoculture rice. Upland rice planted at a smaller distance with sengon is hampered by its growth because the sengon canopy is large and dense, so sunlight does not reach the rice.…”
Section: Growth Of Sengon and Upland Ricementioning
confidence: 99%
“…The types of agroforestry that are widely developed by the community are sengon with upland rice [18][19][20], sengon with chilies [21], sengon with beans [22,23], sengon with soybeans [24,25], sengon with bananas [26], sengon with cassava [27], sengon with patchouli and [28] sengon with citronella plants [29].…”
Section: 23mentioning
confidence: 99%